Determination of Deformation Behaviors and Energy Absorption of Lightweight Composite Lattice Cylinders With Different Structures - Ilyas Bozkurt (International Journal of Polymer Science)
The aim of this study is to determine the crushing performance of four different composite lattice cylinder structures (hexagonal, circular, square, and triangular) under quasistatic compression loading using the finite element method. The numerical model was developed by performing progressive damage analysis with the MAT-54 material model in the LS-DYNA finite element software. The crushing performance (peak force (PF), mean crushing force (MCF), crushing force efficiency (CFE), and specific energy absorption (SEA)) and damage types of composite cylinders for different lattice structures, specimen thicknesses, lengths, material types and compression directions (axial and tangential) were determined and compared with results from other studies in the literature. At the end of the study, it was determined that the PCF value of the square lattice structure was 19.3% higher than hexagonal lattice structure, 37.6% higher than the circular lattice structure, and 33.4% higher than triangular lattice structure for axial loading. The AL specimen exhibited the highest EA value with 171 J, while the CFRP specimen had the highest SEA value with 4.2 J/g. The CFE value was the highest for the AL specimen. The deformation behavior of lattice cylinders varied primarily according to the cell type.